Pre-Exposure Prophylaxis (PrEP) for College Students - Jones, Kenneth (My University, 2022)
Sexual Transmitted Infections (STIs) are a growing risk for large universities and college students. Most STIs are curable; however, the Human Immunodeficiency Virus (HIV) is not. It should be a priority for universities and colleges to integrate screening of HIV cases into their available health services. The purpose of the quality improvement project is to implement a standardized screening tool to identify university students who engage in high-risk sexual activities and are eligible for PrEP. The results show that the proposed improvement tool led to the identification of 21 most at-risk students from a sample of 285. A survey of providers revealed a preference for the PrEP screening tool. Clinic nurses also demonstrated an enhanced understanding of the PrEP screening concepts and suggested strategies for improving the rendering of the related services. In conclusion, the proposed quality improvement project can be replicated at student health services of any university or college to identify students at risk for contracting HIV and reducing the risk of that infection via prescribing of PrEP
Keywords: student health services, risk screening, pre-exposure prophylaxis, HIV, sexually transmitted infections